Original paperClinical and morphological features of patients who underwent endovascular interventions for lower extremity arterial occlusive diseases - Arslan, Sakir; Yuksel, Isa Oner; Koklu, Erkan; Cagirci, Goksel; Ureyen, Cagin; Bayar, Nermin; Kucukseymen, Selcuk; Kus, Gorkem (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: Patients with peripheral arterial disease (PAD) are at increased risk for all-cause mortality and cardiovascular mortality. Aim: To present anatomical and morphological characteristics of patients who underwent endovascular stenting with laboratory and our mid-term results. Material and methods: One hundred fifty-three patients (mean age: 62.8, 86% male) who underwent percutaneous intervention of lower extremity arteries were included in the study. Demographic characteristics, medical history, physical examination and laboratory findings of patients were analyzed. Patients’ lesions were classified according to the TransAtlantic Inter-Society Consensus (TASC). Clinical outcomes included complications and mortality, 6-minute walking distance, functional class (NYHA) and patency rates. Results: Seventy percent of patients had hypertension, 42% were smokers, 78% had coronary artery disease, 20% had coronary artery bypass grafting, 55% had diabetes mellitus and 71% had dyslipidemia. Six patients with diabetes mellitus and poor wound healing despite medical therapy were treated with stenting leading to alleviation of pain and avoidance of amputation. The initial technical success rate of revascularization was 95.6% (153/160). Our mid-term results show that percutaneous procedures in lower extremity arterial diseases can be performed with low complication and high success rates. Patients’ 6-minute walk distance, ankle/brachial index values, functional class and the status of foot ulcers were evaluated. Conclusions: Especially in patients with distal vascular disease, poor wound healing and no chance of surgical revascularization, percutaneous endovascular revascularization may provide good blood flow and prevent amputation.